LOVE IN THE ABSENCE OF JUDGMENT - Beran, Ondřej (Johns Hopkins University, 2019)
This paper discusses the question of whether a philosophical account of love can proceed independently of a judgment about the beloved's value (qualities) or what promotes his or her well-being. I start by introducing a common philosophical problem of how one can love those who are not lovable. I use an example from Death on the Nile to show a different variety of love for an unlovable person. Christie's narrative highlights nonjudgmental loyalty and equality between the lovers as its essential aspects. To show the distinctiveness of this loyalty-based notion of love, I pair it with accounts likely to be sympathetic to it.
Keywords: love; loyalty; equality